Neurosyphilis with positive anti-N-methyl-D-aspartate receptor antibody: a case report - Sha, Zhu; Jing, Shi; Feng, Gao; Hongjun, Hao; Xianzeng, Liu (Frontiers in Neurology, 2023)
A case of neurosyphilis with a positive anti-N-methyl-D-aspartate receptor (NMDAR) antibody was reported. A 54-year-old man who presented with acute memory deficits was admitted to our hospital. Acute ischemic stroke (AIS) was initially considered, and he was prescribed intravenous thrombolysis with recombinant tissue-type plasminogen activator (rt-PA). However, the intermittent onset of episodic memory and orientation disorder still occurred. No diffusion restriction was indicated by magnetic resonance imaging (MRI), and subclinical seizures were frequently found by electroencephalogram (EEG). Rapid plasma reagin (RPR) test of serum showed positive results for syphilis. Analysis of cerebrospinal fluid (CSF) revealed elevated leukocyte count and protein level. RPR test, Treponema pallidum particle agglutination (TPPA) assay, and Treponema pallidum antibody (TP-Ab) in CSF showed positive results, and the anti-NMDAR antibodies were positive in CSF and serum. Finally, the patient was diagnosed with neurosyphilis with a positive anti-NMDAR antibody. The clinical symptoms were improved, and the leukocyte count in CSF was reduced after treatment with intravenous penicillin G and levetiracetam. This case suggests that in cases with positive results for neurosyphilis and NMDAR antibodies, the proper treatment has to be decided based on all of the available clinical and diagnostic testing data.